Electrochemical potential of the inner mitochondrial membrane and Ca(2+) homeostasis of myometrium cells - Yu. V. Danylovych; S. A. Karakhim; H. V. Danylovych; O. V. Kolomiets; S. O. Kosterin (The Ukrainian Biochemical Journal, 2015)
We demonstrated using Ca2+-sensitive fluorescent probe, mitochondria binding dyes, and confocal laser scanning microscopy, that elimination of electrochemical potential of uterus myocytes’ inner mitochondrial membrane by a protonophore carbonyl cyanide m-chlorophenyl hуdrazone (10 μM), and by a respiratory chain complex IV inhibitor sodium azide (1 mM) is associated with substantial increase of Ca2+ concentration in myoplasm in the case of the protonophore effect only, but not in the case of the azide effect. In particular, with the use of nonyl acridine orange, a mitochondria-specific dye, and 9-aminoacridine, an agent that binds to membrane compartments in the presence of proton gradient, we showed that both the protonophore and the respiratory chain inhibitor cause the proton gradient on mitochondrial inner membrane to dissipate when introduced into incubation medium. We also proved with the help of 3,3′-dihexyloxacarbocyanine, a potential-sensitive carbocyanine-derived fluorescent probe, that the application of these substances results in dissipation of the membrane’s electrical potential. The elimination of mitochondrial electrochemical potential by carbonyl cyanide m-chlorophenyl hуdrazone causes substantial increase in fluorescence of Ca2+-sensitive Fluo-4 AM dye in myoplasm of smooth muscle cells. The results obtained were qualitatively confirmed with flow cytometry of mitochondria isolated through differential centrifugation and loaded with Fluo-4 AM. Particularly, Ca2+ matrix influx induced by addition of the exogenous cation is totally inhibited by carbonyl cyanide m-chlorophenyl hydrazone. Therefore, using two independent fluorometric methods, namely confocal laser scanning microscopy and flow cytometry, with Ca2+-sensitive Fluo-4 AM fluorescent probe, we proved on the models of freshly isolated myocytes and uterus smooth muscle mitochondria isolated by differential centrifugation sedimentation that the electrochemical gradient of inner membrane is an important component of mechanisms that regulate Ca2+ homeostasis in myometrium cells.